1996
DOI: 10.1007/bf00121363
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of identical new mutation in the evolutionary landscape

Abstract: In contrast to the common assumption that each new mutant results from a unique, independent mutation event, clusters of identical premeiotic mutant alleles are common. Clusters can produce large numbers of related individuals carrying identical copies of the same new genetic change. By entering the gene pool in multiple copies at one time, clusters can influence fundamental processes of population genetics. Here we report evidence that clusters can increase the arrival and fixation probabilities and can lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 61 publications
1
36
0
Order By: Relevance
“…Thus the starting frequency of a new allele should be c /2 N on average instead of 1/2 N for a population with N individuals, i.e., p = c /2 N [15] . This affects the average survival time of a mutant allele, and formula (3) should be modifi ed as…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the starting frequency of a new allele should be c /2 N on average instead of 1/2 N for a population with N individuals, i.e., p = c /2 N [15] . This affects the average survival time of a mutant allele, and formula (3) should be modifi ed as…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown the existence of clusters in many organisms, such as Drosophila , mice and humans [13][14][15][16][17][18][19][20][21][22][23] . In humans, premeiotic clusters of mutation are common and have been reported for base-pair changes, deletions, insertions, duplications, chromosome rearrangements, trinucleotide repeats and aneuploidy [15,20,[22][23][24] . In a literature survey of 22 genetic syndromes in humans, a new mutation arose from a germinal mosaic parent in eleven percent of the cases (266 families out of 2,459 total families; details can be obtained from the authors).…”
Section: Introductionmentioning
confidence: 99%
“…The mutation screening experiment employs a three-generation assay to screen autosomal recessive lethal or nearly lethal mutations in about 1,200 genes in D. melanogaster (18), which takes advantage of the balancer chromosomes that were pioneered by H. J. Muller for the purpose of maintaining newly isolated mutations, including recessive lethals, without selection (21,22). Balancers for each of the major chromosomes of D. melanogaster contain multiple inversions and one or more dominant visible mutations.…”
Section: Methodsmentioning
confidence: 99%
“…A similar mating scheme as described above was used successfully in earlier assays for the occurrence of mutation clusters in several laboratories (17,18,(25)(26)(27). It was estimated that lethal or nearly lethal mutations identified by the assay span over about 1,200 genes.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, such information can be obtained from traditional experiments, particularly for some model organisms. For Drosophila, multigeneration mutation screening has been well developed (Muller 1928;Woodruff et al 1984Woodruff et al , 1996Ashburner 1989;Greenspan 1997) and one such system was used by Gao et al (2011) for the purpose of identifying recessive lethal or nearly lethal mutations. More experimental detail can be found in Gao et al (2011) and for the main purpose of this article, it should suffice to outline the structure of information and the type of mutation being examined.…”
Section: Definitions and Notationsmentioning
confidence: 99%